2022
DOI: 10.1002/wsb.1255
|View full text |Cite
|
Sign up to set email alerts
|

Is lead‐free .22 long rifle ammunition worth a shot?

Abstract: Scavengers may ingest lead bullet fragments embedded in carcasses and offal left behind from hunting. Most studies focus on big game hunting as a primary source of lead exposure. Yet, millions of small mammals are shot annually for damage control and recreation. Ammunition manufacturers have responded to new regulations and accompanying hunter demand for lead‐free bullets by introducing new products. Yet, few lead‐free bullets are commercially available for the .22 long rifle, despite being the most popular ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Indeed, unpublished research in the UK has found that there is no difference in the depth of penetration of 3.2 mm steel and 2.6 mm lead shotgun pellets in 10% ballistics gelatin covered in animal skin/feathers as a result of the soft lead pellets dragging feathers into the wound channel and retarding penetration (Champion 2021). There remain concerns over the effectiveness of nonlead ammunition for smaller caliber (rimfire) rifles, but there are an increasing number of alternatives which appear to offer satisfactory performance (Hampton et al 2020, McTee and Ramsey 2022).…”
Section: Constraints To Progressmentioning
confidence: 99%
“…Indeed, unpublished research in the UK has found that there is no difference in the depth of penetration of 3.2 mm steel and 2.6 mm lead shotgun pellets in 10% ballistics gelatin covered in animal skin/feathers as a result of the soft lead pellets dragging feathers into the wound channel and retarding penetration (Champion 2021). There remain concerns over the effectiveness of nonlead ammunition for smaller caliber (rimfire) rifles, but there are an increasing number of alternatives which appear to offer satisfactory performance (Hampton et al 2020, McTee and Ramsey 2022).…”
Section: Constraints To Progressmentioning
confidence: 99%
“…This lack of research is a direct consequence of the fact that there are not many types of lead-free 22lr cartridges available. Two examples of evaluations are the article from McTee and Ramsey, 12 which gives a short comparison of one lead-free 22lr cartridge with a number of leadbased cartridges evaluated in hunting rifles, and Hampton et al, 7 where the hunting performance of the same type of lead-free ammunition is evaluated. Most ammunition reviews are, however, given in popular science magazines or as video reviews on YouTube.…”
Section: Introductionmentioning
confidence: 99%